Particle size effects on yttrium aluminum garnet (YAG) phase formation by solid-state reaction. Issue 19 (14th October 2014) - Kupp, Elizabeth R.; Kochawattana, Sujarinee; Lee, Sang-Ho; Misture, Scott; Messing, Gary L.
Abstract